The Influence of Learning Discipline, Anxiety, and Self-Efficacy through Critical Thinking Ability on the Mathematical Reasoning Ability of Eighth-Grade Students at UPTD SMPN 2 Barru - Amaliah, Asri Ainun; Talib, Ahmad; Rosidah, Rosidah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
Mathematical reasoning skills are essential in understanding mathematical concepts and solving problems. This study aims to examine the influence of learning discipline, mathematical anxiety, and self-efficacy on students' mathematical reasoning ability through critical thinking skills. The study utilized an ex-post facto research design with a sample of 100 eighth-grade students from UPTD SMPN 2 Barru. Data were collected through questionnaires on learning discipline, mathematical anxiety, and self-efficacy, as well as critical thinking and mathematical reasoning tests. The findings indicate that learning discipline, mathematical anxiety, and self-efficacy significantly influence mathematical reasoning ability both directly and indirectly through critical thinking skills. Moreover, students with high discipline tend to have better reasoning skills, while those with high mathematical anxiety demonstrate lower reasoning ability. The study suggests that improving students' learning discipline and self-efficacy while reducing mathematical anxiety can enhance their mathematical reasoning ability.